Immunogenic and antigenic heterogeneity of blastocystis sp. Subtype 3 from symptomatic and asymptomatic individuals - Michael, Sheela Devi; Govind, Suresh Kumar (Malaysian Society of Parasitology and Tropical Medicine, 2019)
Blastocystis sp. subtype 3 (ST3) has been implicated previously to be phenotypically heterogeneous between isolates from symptomatic and asymptomatic persons in previous studies. The aim of this study is to identify the immunogenic and antigenic heterogeneity among three different isolates of Blastocystis sp. ST3 isolated from asymptomatic and symptomatic individuals. Immunogenic and antigenic profile of ST3 isolates was assessed through splenocyte proliferation, cytokine assessment and antibody measurements. The total IgG antibody responses in mice immunised with symptomatic (0.736±0.033) and asymptomatic (0.426±0.025) of ST3 Blastocystis sp. were significantly higher compared to the controls respectively. High secretions of IgG antibody mixture of IgG1/IgG2a antibodies were detected in sera of mice immunised with symptomatic and asymptomatic solubilised Blastocystis sp. Antigen (Blastocystis-Ag). Predominant IgG1 production was detected higher in mice injected with Blastocystis sp. ST 3 from asymptomatic individuals (0.148±0.016) (P<0.05) whereas predominant IgG2a production was detected higher in mice injected with the same subtype but from the symptomatic individuals (0.355±0.021). This data was supported by the production of significantly higher Th1 (IFNγ and IL-2) response (393.56±49.21) and (628.89±31.06) respectively in symptomatic isolates compared to Th2 (IL-4 and IL-10) response (93±7.85) and (103.22±11.33) in asymptomatic isolates after in-vitro stimulations. Splenocyte stimulation index (SI) was detected higher in symptomatic Blastocystis-Ag group. This study is the first to demonstrate antigenic and immunogenic heterogeneity among ST3 symptomatic and asymptomatic Blastocystis-Ag with symptomatic isolates being highly immunogenic and antigenic. No significant variations among the three isolates of asymptomatic and symptomatic groups. The study supports the suggestion from previous study that surface variations between symptomatic and asymptomatic isolates as well their distinct phenotypic variation despite being the same subtype may have caused the differences in the distinct immune responses. © 2019, Malaysian Society for Parasitology. All rights reserved.